The Best of I witness : volume 3 - GMA (Quezon City : Felta Multi-media, 2006)
Contents : 1. Gutom / Jay Taruc.-- 2. Magdalenang bukid / Kara David.-- 3. Boy pusit / Sandra Aguinaldo.-- 4. Multo ng nakaraan / Howie Severino.-- 5. Image plugs of I-witness.-- 6. Profiles of the documentarist.
Keywords: Documentary